Uji Angka Kapang Khamir (AKK) dan Angka Lempeng Total (ALT) pada Jamu Kunyit Asam Kemasan Serbuk: Test of Yeast and Mold Count (YMC) and Total Plate Count (TPC) On Powdered Jamu Kunyit Asam - Wildan Zakaria; Rachmi Ridho (Universitas Gunadarma, 2026)
A famous traditional herbal cure created from natural materials, turmeric and tamarind herbal medicine (jamu turmeric tamarind) is now readily available in powder form. The purpose of this study is to evaluate the safety and quality of powdered turmeric and tamarind herbal medicine by looking at factors including water content, total phenolic content, and microbiological contamination. Six brands of commercially available powdered turmeric and tamarind herbal medicine were the subject of an experimental laboratory investigation. The Folin–Ciocalteu method was used to determine the total phenolic content, the gravimetric technique was used to measure the water content, and the pour plate method was used to conduct the Yeast Mold Count (YMC) and Total Plate Count (TPC) assays. The findings indicated that all samples had AKK values ​​between <1 and 1.7 × 10¹ cfu/g and ALT values ​​between <1 and 1.2 × 10⁴ cfu/g, both of which were below the upper limit established by BPOM Regulation Number 29 of 2023. Significant variations were observed in the total phenolic levels among the samples; the maximum value was 121.03 mg GAE/g, while other samples had extremely low values. All of the samples met the quality requirements for natural medical powder formulations since their water contents ranged from 0.62 to 7.20%, which is less than 10%. The analyzed powdered turmeric and tamarind herbal medicine satisfies microbiological safety and quality criteria, has an acceptable water content, and exhibits a range of bioactive potential, according to these findings.